Particle and Particle-Surfactant Mixtures at Fluid Interfaces: Assembly, Morphology, and Rheological Description. (20th August 2015) - Maestro, Armando; Santini, Eva; Zabiegaj, Dominika; Llamas, Sara; Ravera, Francesca; Liggieri, Libero; Ortega, Francisco; Rubio, Ramón G.; Guzman, Eduardo
Abstract : We report here a review of particle-laden interfaces. We discuss the importance of the particle's wettability, accounted for by the definition of a contact angle, on the attachment of particles to the fluid interface and how the contact angle is strongly affected by several physicochemical parameters. The different mechanisms of interfacial assembly are also addressed, being the adsorption and spreading the most widely used processes leading to the well-known adsorbed and spread layers, respectively. The different steps involved in the adsorption of the particles and the particle-surfactant mixtures from bulk to the interface are also discussed. We also include here the different equations of state provided so far to explain the interfacial behavior of the nanoparticles. Finally, we discuss the mechanical properties of the interfacial particle layers via dilatational and shear rheology. We emphasize along that section the importance of the shear rheology to know the intrinsic morphology of such particulate system and to understand how the flow-field-dependent evolution of the interfacial morphology might eventually affect some properties of materials such as foams and emulsions. We dedicated the last section to explaining the importance of the particulate interfacial systems in the stabilization of foams and emulsions.